Virtual reality as a training tool in engineering education - Arshad, Haslina; Hamouda, Abdel Magid Salem; Ismail, Napsiah; Sulaiman, Riza (Inderscience Enterprises, 2008)
This paper presents a new desktop training tool in Flexible Manufacturing Cell (FMC) to demonstrate and address the concept of reconfigurability of Flexible Manufacturing System (FMS). It is a robot‐centred desktop virtual system with three main elements consisting of a milling machine, a storage system and a six degrees of freedom articulated robot. Visual C++ and OpenGL are used for user interface, simulation and animation. During simulation, the elements of the FMC are re‐configured by changing the position of the storage system through the configuration interface. This system can provide visualisation of the reconfiguration process of the FMC and a good training tool for students.